KOMPARASI METODE BLENDED LEARNING DENGAN METODE TPR DALAM KEEFEKTIFANNYA TERHADAP SISTEM PEMBELAJARAN DARING PADA MATERI VOCABULARY BAHASA INGGRIS - Sri Wilda Harahap; Berkat Panjaitan (Jurnal Mutiara Pendidikan Indonesia, 2021)
Vocabulary is one of the important aspects of learning a foreign language. With limited vocabulary one will also have a limited understanding of speaking, reading, listening, and writing. This condition requires creative teachers to use the most appropriate and appropriate learning methods in accordance with the material being studied to achieve learning goals and outcomes. This study aims to compare blended learning methods with total physical responses (TPR) methods about their effectiveness in learning English vocabulary materials at DRA Islamic School. . The results of this study showed that the TPR Method Mean 75, Standard Deviation 10.12739, While blended learning method mean 69.75, standard deviation 7.675302. The above hypothesis test obtained the P-value of 0.010765. It was concluded that there are differences in vocabulary material learning outcomes using TPR methods and Blended Learning Methods. Where the TPR method is more effective than the Blended Learning method in learning English vocabulary material in students in the 2nd grade of DRA Islamic School online.